2014
DOI: 10.7554/elife.04664
|View full text |Cite
|
Sign up to set email alerts
|

Early asymmetric cues triggering the dorsal/ventral gene regulatory network of the sea urchin embryo

Abstract: Dorsal/ventral (DV) patterning of the sea urchin embryo relies on a ventrally-localized organizer expressing Nodal, a pivotal regulator of the DV gene regulatory network. However, the inceptive mechanisms imposing the symmetry-breaking are incompletely understood. In Paracentrotus lividus, the Hbox12 homeodomain-containing repressor is expressed by prospective dorsal cells, spatially facing and preceding the onset of nodal transcription. We report that Hbox12 misexpression provokes DV abnormalities, attenuatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 64 publications
(126 reference statements)
3
37
1
Order By: Relevance
“…Abundant comparative evidence exists for other euechinoid taxa as well, including Lytechinus variegatus (Lv) (31)(32)(33)(34)(35)(36)(37) and Paracentrotus lividus (Pl) (38)(39)(40)(41)(42). Data from these indirectdeveloping euechinoids indicate that although these taxa diverged from one another ∼90 mya (9, 43), very little appreciable change to their developmental GRNs has accrued (44)(45)(46).…”
mentioning
confidence: 99%
“…Abundant comparative evidence exists for other euechinoid taxa as well, including Lytechinus variegatus (Lv) (31)(32)(33)(34)(35)(36)(37) and Paracentrotus lividus (Pl) (38)(39)(40)(41)(42). Data from these indirectdeveloping euechinoids indicate that although these taxa diverged from one another ∼90 mya (9, 43), very little appreciable change to their developmental GRNs has accrued (44)(45)(46).…”
mentioning
confidence: 99%
“…In this regard, we have shown in P. lividus that the Hbox12 homeodomain repressor is expressed by prospective dorsal ectoderm cells, spatially facing and preceding the onset of nodal transcription, where it acts preventing the ectopic activation of nodal expression [51][52][53][54]. Functional analysis revealed that expression of hbox12 and nodal genes are mutually exclusive and both required for DV polarization.…”
Section: Nodal-expressing Organizing Centrementioning
confidence: 98%
“…Functional analysis revealed that expression of hbox12 and nodal genes are mutually exclusive and both required for DV polarization. In fact, overexpression of Hbox12 specifically attenuates nodal transcription, while loss of Hbox12 function allows broad ectopic expression of nodal, and in both the experimental assays the resulting embryos do not acquire DV polarity [53,54]. Intriguingly, Hbox12 is functionally upstream of p38, being specifically involved in the transient inactivation of the kinase in dorsal blastomeres [53].…”
Section: Nodal-expressing Organizing Centrementioning
confidence: 99%
See 2 more Smart Citations